2008
DOI: 10.1634/stemcells.2008-0153
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Death of Adult Hippocampal Neural Stem Cells Following Insulin Withdrawal

Abstract: Novel therapeutic approaches using stem cell transplantation to treat neurodegenerative diseases have yielded promising results. However, survival of stem cells after transplantation has been very poor in animal models, and considerable efforts have been directed at increasing the viability of engrafted stem cells. Therefore, understanding the mechanisms that regulate survival and death of neural stem cells is critical to the development of stem cell-based therapies. Hippocampal neural (HCN) stem cells derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
95
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 46 publications
10
95
0
2
Order By: Relevance
“…13 Insulin withdrawal-induced HCN cell death was characterized by multiple complementary assays, e.g., cell morphology, propidium iodide (PI) staining, cell viability assay dependent on mitochondrial metabolic activity, and cell proliferation assay employing BrdU incorporation. 13 Insulin withdrawal typically induces more than 50% of cell death at day 3, when assessed by PI staining. Interestingly, even after 3 days of insulin withdrawal caspases-3 activation or chromosomal DNA fragmentation is not observed.…”
Section: Autophagic Cell Death In Hippocampal Neural Stem (Hcn) Cellsmentioning
confidence: 99%
“…13 Insulin withdrawal-induced HCN cell death was characterized by multiple complementary assays, e.g., cell morphology, propidium iodide (PI) staining, cell viability assay dependent on mitochondrial metabolic activity, and cell proliferation assay employing BrdU incorporation. 13 Insulin withdrawal typically induces more than 50% of cell death at day 3, when assessed by PI staining. Interestingly, even after 3 days of insulin withdrawal caspases-3 activation or chromosomal DNA fragmentation is not observed.…”
Section: Autophagic Cell Death In Hippocampal Neural Stem (Hcn) Cellsmentioning
confidence: 99%
“…Autophagy may also promote survival by clearance of damaged organelles or protein aggregates in stressed cells (Abedin et al, 2007;Colell et al, 2007). Alternately, autophagy can induce cell death and autophagic death has been observed in cells in which caspases have been inhibited (Yu et al, 2004) and has also been implicated in the death of Drosophila larval salivary glands (Lee and Baehrecke, 2001), the elimination of cells in the inner cell mass of blastocysts (Qu et al, 2007), and the death of insulin-deprived neural stem cells (Yu et al, 2008).The Bcl-2 family of proteins regulate cell death upon growth factor withdrawal and is critical in the regulation and function of both apoptosis and autophagy. Anti-apoptotic Bcl-2 family proteins such as Bcl-2 and Bcl-xL are up-regulated by growth factors and are frequently overexpressed in cancer (Walensky, 2006).…”
mentioning
confidence: 99%
“…However, as previous studies reported, the expression of beclin1 is augmented significantly when autophagy is induced [22,27]. This discrepancy may be due to the difference in cell types, stimuli, and duration of treatment applied to individual studies.…”
Section: Discussionmentioning
confidence: 78%